2015
DOI: 10.1055/s-0034-1377835
|View full text |Cite
|
Sign up to set email alerts
|

Sedation in gastrointestinal endoscopy: a prospective study comparing nonanesthesiologist-administered propofol and monitored anesthesia care

Abstract: Introduction: Adequate sedation is one of the cornerstones of good quality gastrointestinal endoscopy (GIE). Propofol sedation has increased significantly but there has been much debate over whether it can be administered by endoscopists. The aim of this prospective trial was to compare nonanesthesiologist-administered propofol (NAAP) and monitored anesthesia care (MAC). Methods: A total of 2000 outpatients undergoing GIE at Hospital Albert Einstein (São Paulo, Brazil), a tertiary-care private hospital, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
2
15
1
1
Order By: Relevance
“…To calculate the sample size for this study, the incidence of adverse cardiopulmonary events including hypotension and hypoxemia was assumed to be approximately 34% for propofol sedation, as was found in a previous study [17]. Power analysis with α = 0.05 and β = 0.2 to determine a 50% reduction in adverse cardiopulmonary events with meperidine and midazolam revealed that each group required a minimum of 36 patients.…”
Section: Methodsmentioning
confidence: 99%
“…To calculate the sample size for this study, the incidence of adverse cardiopulmonary events including hypotension and hypoxemia was assumed to be approximately 34% for propofol sedation, as was found in a previous study [17]. Power analysis with α = 0.05 and β = 0.2 to determine a 50% reduction in adverse cardiopulmonary events with meperidine and midazolam revealed that each group required a minimum of 36 patients.…”
Section: Methodsmentioning
confidence: 99%
“…5 Flinders Medical Centre, Bedford Park, South Australia, Australia. 6 Department of Anaesthesia, The Queen Elizabeth Hospital, Woodville, South Australia, Australia. 7 Human Physiology Anaesthesia and Intensive Care, School of Medicine and Public Health, The University of Newcastle, Callaghan, New South Wales, Australia.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Reasons for desaturation during ERCP under deep sedation have been attributed to reduced cardiopulmonary reserve, advanced age, respiratory depression, duration of the procedure, and prone positioning. The incidence of hypoxemia during any endoscopic procedure is in the range of 11%-50% [5][6][7] and it is possibly as high as 60% with ERCP [8] (definitions of hypoxia vary between the studies). Prolonged hypoxia is a major risk factor for periprocedural cardiac arrhythmias and myocardial ischaemia [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moderate to deep sedation is a commonly employed technique for ERCPs, with general anaesthesia utilising an endotracheal intubation being reserved for selected cases. Reported rates of hypoxemia during all endoscopic procedures range from 11 to 50% [1][2][3], and this may be as high as 60% with ERCP [4]. (Definitions of hypoxia vary between the studies.)…”
Section: Introductionmentioning
confidence: 99%